AB0816 Efficacy of biological agents in the treatment of idiopathic retroperitoneal fibrosis. (23rd January 2014) - Catanoso, M.; Magnani, L.; Spaggiari, L.; Pipitone, N.; Caruso, A.; Addimanda, O.; Meliconi, R.; Pulsatelli, L.; Versari, A.; Boiardi, L.; Vaglio, A.; Pattacini, P.; et al.
Abstract : Objectives: Glucocorticoids (GCs) are the most used drugs for the treatment of idiopathic retroperitoneal fibrosis (IRF).Several steroid-sparing agents, including immunodepressants and tamoxifen, have been used with varying success. However, some patients are resistant to these therapies and valuable medical treatments are not available.The aim of this study was to assess the efficacy and safety of the anti-IL-6 receptor (IL-6R) antibody tocilizumab (TCZ) in patients with IRF. Methods: Two patients received monthly TCZ infusions (8 mg/kg bodyweight) for six consecutive months.One of the patients treated with TCZ was previously unsuccessfully treated with IFX and abatacept and one patient was naive to biological agents.Disease activity and drug tolerability were assessed every month clinically and by laboratory tests such as ESR, CRP, IL-6, and the IL-6 soluble receptor (sIL-6R).18F-fluorodeoxyglucose PET (PET/CT) and abdominal Compurerized Tomography(CT)-scans were used for monitoring disease activity and treatment response. Results: All two patients had a satisfactory clinical and laboratory response with a significant improvement of CT and PET findings.A reduction of retroperitoneal mass greater than 25% was observed in all patients. Remission maintenance therapy with MTX (20 mg/weekly)was started in all two patients. No serious adverse events were noted Conclusions: TCZ is potentially effective treatments for patients with IRF that warrants evaluation in randomized trials. Disclosure of Interest: None Declared